The Piano: A Psychoanalytic Approach to Movie as A Media of Reflective Teaching - Erna Wardani (J-Lalite: Journal of English Studies, 2020)
Freud’s psychoanalytic approach has been one of the most controversial approaches to many fields of interest. Relating to education and educational psychology, this approach plays a significant role in modifying and enhancing one’s behavioral relationship among the educational elements like educators, parents, and students. Therefore, in many things, this approach has contributed a lot of inspiration in the development of education. In literary works, there seems to be a mutual fascination between psychoanalysis and literature whereas theory and approach, psychoanalysis explains literature and literature itself exploits psychoanalysis for creative purposes and works. Here, as a creative work, movie is considered literature because it can be interpreted and analyzed just like other written works of literature. As a learning instrument, movie evokes an affective domain that leads to changes in learning behavior and attitudes. Experiencing certain-themed movies can trigger particular reflective memories and reference toward events occurring on a daily basis and it can further strengthen the foundation for learning complex concepts like psychoanalysis.